Prospective surveillance after implementation of a colorectal surgical site infection prevention bundle. (28th May 2021) - Jurt, J; Clerc, D; Curchod, P; Hübner, M; Hahnloser, D; Senn, L; Demartines, N; Grass, F
Abstract: Objective: Surgical site infections (SSI) are the most frequent complications after colorectal surgery. The aim of the present study was to evaluate the impact of a standardized SSI prevention bundle. Methods: The multimodal, evidence-based care bundle included 9 intraoperative items (antibiotic type, timing and re-dosing, desinfection, induction temperature control >36.5°, glove change, intracavity lavage, wound protection and closure strategy). The bundle was implemented in November 2018 and applied to all consecutive patients undergoing colonic resections. Demographics, surgical specifics and overall compliance to the care bundle were prospectively assessed until October 2020. The primary outcome SSI was defined according to the definition of the Center for Disease Control (CDC) and independently assessed by the National Infection Surveillance Committee (Swissnoso) up to 30 postoperative days. A historical, institutional pre-implementation control group (2012-2017, DOI: 10.1016/j.jhin.2018.09.011) with identical methodology was used for comparison. Results: In total, 243 patients were included. The control group included 1'263 patients. Both groups were comparable regarding main demographics (age, sex, body mass index, American Society of Anaesthesiologists class) and surgical characteristics (type and duration of surgery). Overall compliance to the care bundle was 77% (IQR 77-88). Lowest compliance was observed for temperature control (48%), intracavity lavage (59%) and predefined wound closure strategy (74%). Surgical site infections were reported in 54 patients (22.2%) vs. 21.4% in the control group, p = 0.79. Infection rates were comparable throughout the CDC categories: superficial: 11 patients (4.5%) vs. 4.2%, p = 0.82, deep incisional: 9 patients (3.7%) vs. 5.1%, p = 0.34, organ space: 34 (14%) vs. 12.4%, p = 0.48. Conclusion: Implementation of a standardized surgical care bundle had no impact on SSI rates according to these preliminary results. Improved compliance to individual measures may help to achieve a clinical benefit.